The research-practice divide in beginning reading - Spear-Swerling, Louise (Theory into Practice, 2007)
An extensive research base on beginning reading acquisition and reading difficulties, developed over the past few decades, has important implications for the teaching of reading. Unfortunately, much of this research does not appear to be reaching teachers, whose knowledge is essential for scientific findings about reading to benefit children. This article focuses on two key areas of teachers' research-based disciplinary knowledge for teaching reading: knowledge about children's early reading development and knowledge about English word structure. Evidence demonstrating a gap between teacher knowledge in these areas and current scientific findings is reviewed. Next, possible reasons for the gap are explored. The article concludes with suggestions for educators who are interested in acquiring additional research-based knowledge about reading.
Keywords: dept.rdg; dept.sed